A Comparative Study of Efficacy and Safety of Myo Inositol versus Metformin in Polycystic Ovarian Syndrome in Women - Sadia Wazir, Faiza Rahman, Razia Bibi, Tariq Hassan, Komal Farooqi, Nighat Afridi, (Pakistan Journal of Medical & Health Sciences, 2022)
Objective: This study was aimed to compare the efficacy and safety of Myo inositol versus Metformin in polycystic ovarian syndrome in women. Study design: A retrospective randomized comparative study. Place and Duration: In Gynaecology and Obstetrics Department of Combined Military Hospital, Peshawar for the period from June, 2021 to November, 2021. Methods: The study was conducted on 100 patients that were randomly divided into two groups of 50 each: group A and group Group A was given the treatment: Tab Myoinositol 1gm twice daily and Group B was given: Tab Metformin 500mg thrice daily for six months. While treating women with Polycystic Ovary Syndrome, the efficacy assessment was done on observing menstrual irregularity, clinical (acne, hirsutism), infertility and changes in weight for 6 months. Safety assessment was also done. For statistical analysis, SPSS-20.0 was used. Results: The mean age in group A was 24.6±3.22 years and mean BMI 25.7±4.24 kg/m2 while in group B mean age was 23.12±7.40 years with mean BMI 26.1±4.31 kg/m2. After a period of six months, we found that a significant improvement in all of the symptoms was present in both groups. On the other hand, when looking at the two groups' symptoms at three and six months, there was no discernible difference between them. In terms of its safety profile, myo-inositol came out on top when compared to metformin. Conclusion: Both metformin and myo-inositol have been shown to be effective in treating PCOS. Insulin resistance, irregular menstruation, hyperandrogenism, and infertility are all helped by these medications. Treatments for PCOS were equally effective, relieving symptoms for patients, but a direct comparison showed no clear winner. In comparison to Metformin, myoinositol had a higher rate of patient acceptance. Keywords: PCOS, Infertility, Metformin, Myoinositol, Insulin Resistance, Irregular menstruation